Biodiversity stabilizes primary productivity through compensatory effects under warming conditions. (23rd March 2022) - Li, Chenlan; Jiang, Yuan; Wang, Zihui; Hogan, J. Aaron; Luo, Wenqi; Xu, Han; Chu, Chengjin; Fang, Suqin
Abstract: Aim: Diversity may increase the resistance of ecosystem productivity to environmental stress, such as warming, via compensatory processes associated with adjustments of species interactions. However, experimental evidence of compensatory processes that buffer productivity declines in relation to environmental stress is limited, especially in below‐ground settings. We asked whether species richness could stabilize productivity under warming via compensatory responses in root biomass and root functional traits. Methods: Using three herbaceous species, we created plant communities composed of four individuals in either monocultures or two‐ and three‐species assemblages. We grew them at three temperatures, simulating current climate conditions, moderate warming and severe warming, respectively. We built mixed‐linear mixed models to model plant productivity by species richness and warming and we also analyzed the interactive roles of species richness and warming in species interaction and root functional traits. Results: We found that warming reduced both above‐ and below‐ground productivity and shifted the biodiversity–productivity relationship from negative to positive. Productivity reductions were weaker in richer species combinations. Warming ameliorated the strength of interspecific competition below‐ground in mixed‐species communities by reducing the root biomass of strong competitors, which benefitted root growth of weaker competitors. Conclusions: Our results suggest warming can facilitate compensatory responses in herbaceous root productivity across species competition hierarchies. These compensatory processes by which species richness stabilizes plant community functioning emphasize the importance that plant functional diversity has in maintaining ecosystem functioning with climate change. Abstract : Using three herbaceous species, this study presents experimental evidence that warming reduces both above‐ and below‐ground productivity and can shift the biodiversity–productivity relationship from negative to positive. The underlying mechanism is that warming ameliorates the strength of interspecific competition below‐ground in mixed‐species communities, by reducing the root biomass of strong competitors, which benefits root growth of weaker competitors.